Diaspora in the Cyberspace: Assertion of Identity, Virtual Home, and International Politics - Singh, Jay (Literary Studies, 2023)
Developments in the field of science and technology revolutionized the field of information technology that culminated in the superhighways of internet that enabled not only the fasted transfer of information but also the cyberspace, a virtual world parallel to the physical world. However it is not a neutral space the same power struggles, hierarchies, and hegemonies which are present in the physical world also contaminate the virtual space. This parallel universe though owned by transnational capitalists provides a space and means to register dissenting voices which is central to diaspora narratives along with many other dissenting groups. It provides an opportunity to the otherwise dispersed diaspora groups to meet each other, unite as a comprehensive community, and constitute a virtual nations in the cyberspace. Though it provides a platform to the dissenting voices, it is not neutral and completely benign. According to some scholars it is the strongest tool of neo-colonialism. Despite its negative aspects the cyberspace has emerged as an alternative space alongside physical space and its physical and ideological dimensions are felt across all spheres of life ranging from economic, political, and socio-cultural to innumerable other spheres. To understand this complex relationship between citizens, nation states, indigenous communities, and diaspora in the cyberspace this research paper brings in Benedict Anderson’s idea of imagined communities along with Michael Foucault’s idea of knowledge and power and foregrounds the complexities of the diaspora’s relationship with it.